Prevalence and Susceptibility Profiles Of Staphylococcus Aureus Isolates from Outpatients and Inpatients at UCTH, Calabar, Nigeria - J.U., Otu (International Journal of Scientific Research in Biological Sciences, 2020)
This study determined the prevalence and susceptibility profiles of Staphylococcus aureus isolates from patients at University of Calabar Teaching Hospital (UCTH), Calabar, Cross River State, Nigeria. 120 swab specimens from patients were screened for staphylococci using standard microbiological protocol. Coagulase-positive staphylococci (CoPS) isolates were subjected to 16S rRNA sequencing for further identification. By disk diffusion method, antibiotic susceptibility test was evaluated in all the S. aureus strains. Results revealed that 46 (38.3%) CoPS and 52 (43.1%) coagulase-negative staphylococci (CoNS) were isolated. Morphological and biochemical characterization showed that of the 120 samples used, 98 (81.7%) yielded staphylococci, out of which only 9 strains of S. aureus were identified on the basis of 16S rRNA sequencing. The gender distribution ratio of prevalence of staphylococci was 25:21 (54.3%:45.7%) female to male but with male showing preponderance. There was no significant relationship between sex of patients and prevalence rate of CoPS at significant level (P?0.05). All the S. aureus strains were highly susceptible to ceftriaxone and cefixime and resistant to vancomycin, penicillin and chloramphenicol. There was significant difference (p?0.05) in the resistance patterns of the 9 strains of S. aureus. The results proved that S. aureus isolates from the clinical samples are relatively resistant to commonly used antibiotics. The outcome of this study is useful in moderating the right prescription of antibiotics against S. aureus infections especially in hospital settings.